2011
DOI: 10.19030/cier.v2i4.1070
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration On The Differences In Emotional Intelligence Of First Year Students Examined Across Disciplines Within The School Of Business In A Liberal Arts College

Abstract: In preparing the next generation of business professionals, educators need to take seriously the responsibility of empowering students with tools to assist them in their pursuits.  One area of interest is Emotional Intelligence.  Emotional Intelligence determines how students exercise self-control, zeal and persistence, and the ability to motivate themselves.  The purpose of the study is two-fold with respect to Emotional Intelligence.  First, the researchers will explore the differences of emotional intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Results from this study showed no difference in EI development by major or gender, which is differs from some past studies (Joyner & Mann, 2011;Leedy & Smith, 2012;Yarrish & Law, 2009). However, when the students were divided into groups by their beginning EI levels, there were significant increases in a few EI areas for those beginning with low EI, but no increases for those with high EI.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Results from this study showed no difference in EI development by major or gender, which is differs from some past studies (Joyner & Mann, 2011;Leedy & Smith, 2012;Yarrish & Law, 2009). However, when the students were divided into groups by their beginning EI levels, there were significant increases in a few EI areas for those beginning with low EI, but no increases for those with high EI.…”
Section: Discussioncontrasting
confidence: 94%
“…The research also showed sometimes there were differences by demographic groups, such as gender (Joyner & Mann, 2011;Leedy & Smith, 2012) or major (Yarrish & Law, 2009), and by the beginning level of the students' EI (Kruml & Yockey, 2011).…”
Section: Review Of Ei Teaching Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The first portion of the survey focused on the assessment of the respondent's degree of emotional intelligence was originally generated in Wong, Law, and Song (2002) in a study to determine a psychometrically sound and practically short emotional intelligence measure that could be used in leadership and management studies. The instrument was later modified by Yarrish and Law (2009) according to the four-dimensional definition of emotional intelligence in Davies, Stankov, and Roberts (1998) that investigated the relationship among measures of emotional intelligence, traditional human cognitive abilities, and personality. The four dimensions are self-emotions appraisal, others-emotions appraisal, use of emotion, and regulation of emotion.…”
Section: Methodology: Survey Instrumentsmentioning
confidence: 99%
“…The ability to cope with different social situations and making the best decisions in these situations is a measure of one's emotional intelligence. The fact first-year students uniquely exposed to a greater number of challenges requiring the use of EI in a short period of time, as well as, the fact first-year students of every university yield the highest attrition rates of the student population, necessitated investigation into the relationship between EI and attrition (DeBerard, Spielmans, & Julka, 2004, pg. 3) Such an investigation was undertaken by Yarrish and Law (2009). The purpose of the study was to determine the differences of EI among different majors at a small, liberal arts college.…”
Section: Emotional Intelligence (Ei) and Academicsmentioning
confidence: 99%